2015
DOI: 10.1111/jnc.13146
|View full text |Cite
|
Sign up to set email alerts
|

Input‐specific regulation of hippocampal circuit maturation by non‐muscle myosin IIB

Abstract: Myh9 and Myh10, which encode two major isoforms of non-muscle myosin II expressed in the brain, have emerged as risk factors for developmental brain disorders. Myosin II motors regulate neuronal cytoskeletal dynamics leading to optimization of synaptic plasticity and memory formation. However, the role of these motor complexes in brain development remains poorly understood. Here, we disrupted the in vivo expression of Myh9 and/or Myh10 in developing hippocampal neurons to determine how these motors contribute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 61 publications
1
16
0
Order By: Relevance
“…In developing distal axons, myosin II has well‐characterised roles in growth cone motility (Vallee et al ., ) and sema3A‐induced axon retraction (Gallo, ; Arnold & Gallo, ). In dendrites, it is necessary for spine maturation (Ryu et al ., ; Rubio et al ., ; Koskinen et al ., ), while distinct myosin II isoforms are also critical for the normal maturation of specific dendritic compartments and pathway‐specific synaptic function (Ozkan et al ., ). Myosin II activity is also crucial for the stability of long‐term potentiation (Rex et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…In developing distal axons, myosin II has well‐characterised roles in growth cone motility (Vallee et al ., ) and sema3A‐induced axon retraction (Gallo, ; Arnold & Gallo, ). In dendrites, it is necessary for spine maturation (Ryu et al ., ; Rubio et al ., ; Koskinen et al ., ), while distinct myosin II isoforms are also critical for the normal maturation of specific dendritic compartments and pathway‐specific synaptic function (Ozkan et al ., ). Myosin II activity is also crucial for the stability of long‐term potentiation (Rex et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Consistent with this paradigm, myosin 2B is enriched along with F-actin in spines, and attenuating the myosin's function in developing neurons either pharmacologically or by knockdown results in a strong block in spine maturation (Morales and Fifková, 1989;Ma et al, 2006;Ryu et al, 2006;Rex et al, 2010;Hodges et al, 2011;Rubio et al, 2011;Gavin et al, 2012;Koskinen et al, 2014;Ozkan et al, 2015;Briggs et al, 2018). Moreover, blocking myosin 2B function in fully-developed neurons shows that it also plays a critical role in the activitydependent changes in spine actin morphology underlying learning and memory (Rex et al, 2010;Rubio et al, 2011;Gavin et al, 2012;Ozkan et al, 2015;Briggs et al, 2018). While myosin 2B is present in dendritic filopodia as well as in mature spines (Korobova and Svitkina, 2010), its function in mature spines has been studied most.…”
Section: Introductionmentioning
confidence: 78%
“…in the spine neck and base of the head), most likely in the form of bipolar filaments (Korobova and Svitkina, 2010). The contractile activity of these bipolar filaments is thought to drive the shortening of immature spines during spine maturation, the constriction of the spine neck, the tip-to-base flow of a dynamic spine actin pool, the cross-linking of a stable spine actin pool, and possibly global spine actin dynamics by catalyzing actin filament turnover downstream of myosin-dependent actin filament breakage (Ozkan et al, 2015). Interestingly, Purkinje neurons express an alternatively spliced version of myosin 2B known as myosin 2B-B2 in addition to regular myosin 2B (Ma et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The immunoblot analysis result showed that only the expression of MYH10 was significantly increased, and there was no obvious change in the expression of MYH9. A previous study reported that MYH10 is the major isoform regulating Schaffer collateral inputs [42]; thus, it is likely that the increase in MYH10, but not MYH9, can compensate for most of the functions of MYH14 in cochlea. The results from the MYH14 gene screening revealed one nonsense mutation.…”
Section: Discussionmentioning
confidence: 99%